2006
DOI: 10.2741/1840
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-leukocyte aggregates and derived microparticles in inflammation, vascular remodelling and thrombosis

Abstract: As a result of vascular injury, activated platelets will rapidly interact with circulating platelets, via membrane glycoprotein complex alphaIIbbeta3 (GPIIb-IIIa) and fibrinogen, to form a thrombus or a plug preventing fatal bleeding. In addition, platelets interacting with ruptured atherosclerotic plaques or with the surface of diseased vessels can aggregate and induce ischemia that prevents blood flow. However, increasing evidence has also shown that circulating platelets interact with leukocytes and endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 58 publications
4
42
0
5
Order By: Relevance
“…Relevant studies have also reported a significantly higher percentage of PDMPs in patients with cerebrovascular events relating to large and small vessels than in healthy subjects [26]. PDMPs play a role in the normal hemostatic response to vascular injury, but on the other hand, it is also possible that the local generation of PDMPs in atherosclerotic arteries may promote arterial occlusion [27]. Thus, persistent elevated blood concentrations of PDMPs may be a marker of the increased risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have also reported a significantly higher percentage of PDMPs in patients with cerebrovascular events relating to large and small vessels than in healthy subjects [26]. PDMPs play a role in the normal hemostatic response to vascular injury, but on the other hand, it is also possible that the local generation of PDMPs in atherosclerotic arteries may promote arterial occlusion [27]. Thus, persistent elevated blood concentrations of PDMPs may be a marker of the increased risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…2 Inflammation is believed to play a decisive initial and perpetuating role in the thrombotic transformation of this plaque, 3,4 and platelet activation is central to the formation of thrombus. 5 This increased state of inflammation is mainly paralleled by activation of platelets with surface-exposing P-selectin, which tethers the platelet to monocyte via P-selectin glycoprotein ligand-1 (PSGL-1) to form platelet-monocyte aggregates (PMA). The close interaction between monocytes and platelets leads to leukocyte activation and cell-adhesion molecule expression, and activates the release of enzymes such as Matrix Metalloproteinases (MMPs), which degrade the subendothelial basement membrane, leading to subsequent plaque rupture or thrombogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Platelets are the major cellular component of thrombosis, 2 and patients with HF have enhanced platelet activation, as reflected by increased whole blood aggregation, 3 high mean platelet volume, 4 and increased platelet P-selectin surface exposure. 5 In addition to roles in hemostasis and thrombosis, platelets are also able to regulate the activity of other cell types, and cross-talk between monocytes and platelets is reflected by formation of monocyte-platelet aggregates (MPAs).…”
mentioning
confidence: 99%